Roadmap and Direction toward High-Performance MoS2 Hydrogen Evolution Catalysts - Cao, Yang (ACS nano, 2021)
MoS2 intrinsically show Pt-like hydrogen evolution reaction (HER) performance. Pristine MoS2 displayed low HER activity, which was caused by low quantities of catalytic sites and unsatisfactory conductivity. Then, phase engineering and S vacancy were developed as effective strategies to elevate the intrinsic HER performance. Heterojunctions and dopants were successful strategies to improve HER performance significantly. A couple of state-of-the-art MoS2 catalysts showed HER performance comparable to Pt. Applying multiple strategies in the same electrocatalyst was the key to furnish Pt-like HER performance. In this review, we summarize the available strategies to fabricate superior MoS2 HER catalysts and tag the important works. We analyze the well-defined strategies for fabricating a superior MoS2 electrocatalyst, propose complementary strategies which could help meet practical requirements, and help people design highly efficient MoS2 electrocatalysts. We also provide a brief perspective on assembling practical electrochemical systems by high-performance MoS2 electrocatalysts, apply MoS2 in other important electrocatalysis reactions, and develop high-performance two-dimensional (2D) dichalcogenide HER catalysts not limited to MoS2. This review will help researchers to obtain a better understanding of development of superior MoS2 HER electrocatalysts, providing directions for next-generation catalyst development.